Critical Review of Collaborative Care in Radiological Procedures: Bridging Nursing and Imaging Expertise - Alharbi, Abdulrhman Saad Juailan; Almoutairi, Alanoud Sati Barkan; Al-Harbi, Faisal Suwaileh; Al-Harbi, Rabie Awad; Al Mehmadi, Khalid Mualla; Alharbi, Bandar Abdullah; Humayyim, Jaber Hussain Ali Bin; Binhammem, Abdalrhman Hussein; Binhamim, Mohammed Hussien Ali; Alsuhaymi, Abdulwahab Musaed (Journal of Ecohumanism, 2024)
This paper aims to critically review the collaborative care model applied in radiological processes incorporating the connection between nursing and imaging disciplines. Given this, cooperation with the staff of other healthcare professions emerges as a necessity due to the growing specialization in healthcare delivery. Radiologists, nurses, and imaging technicians are the professionals most involved in radiological procedures, and this review considers how these workers’ teamwork can enhance patient care. This review outlines literature data and recommendations for improving cooperation between the nursing and imaging departments, including its advantages and possible difficulties.